COMMUNITY EMPOWERMENT THROUGH PARTICIPATORY DESIGN AND LOCAL MATERIAL OPTIMALISATION FOR SUSTAINABLE TOURISM - Asharhani, Imaniar Sofia; Hibrawan, Abdullah; Kusuma, Adriyan; Tanjaya, Tanjaya; Wijaya, Christian Wisaputra; Arum, Danielle Ratna (Universitas Muhammadiyah Aceh, 2025)
This community service program focuses on empowering the local community in Desa Setu through the development of Cafe Kampoeng. Using a Participatory Action Research (PAR) approach, the community is actively involved in the design and implementation processes. The program emphasizes the use of local materials such as bamboo, rattan, and wood to produce sustainable and ergonomic furniture. Training workshops were conducted for table, chair, and custom furniture production, integrating ergonomic principles to ensure user comfort and functionality. The results showed increased community skills, improved economic opportunities, and enhanced local tourism potential. This initiative fosters long-term independence and supports sustainable rural tourism development.Keywords: community empowerment, participatory design, local materials, ergonomics, rural tourism